Improvement of the physical performance is associated with activation of NO/PGC-l alpha/mtTFA signaling pathway and increased protein expressions of electron transport chain in gastrocnemius muscle from rats supplemented with L-arginine - Valgas da Silva, Carmem Peres [UNESP]; Delbin, Maria Andreia; La Guardia, Paolo G.; Moura, Carolina Soares; Couto Davel, Ana Paula; Priviero, Fernanda Bruschi [UNESP]; Zanesco, Angelina [UNESP] (Elsevier B.V., 2015)
Aim: To examine the influence of L-arginine supplementation in combination with physical training on mitochondrial biomarkers from gastrocnemius muscle and its relationship with physical performance.Main methods: Male Wistar rats were divided into four groups: control sedentary (SD), sedentary supplemented with L-arginine (SDLA), trained (TR) and trained supplemented with L-arginine (TRLA). Supplementation of L-arginine was administered by gavage (62.5 mg/ml/day/rat). Physical training consisted of 60 min/day, 5 days/week, 0% grade, speed of 1.2 km/h. The study lasted 8 weeks. Skeletal muscle mitochondrial enriched fraction as well as cytoplasmic fractions were obtained for Western blotting and biochemical analyses. Protein expressions of transcriptor coactivator (PGC-l alpha.), transcriptor factors (mtTFA), ATP synthase subunit c, cytochrome oxidase (COXIV), constitutive nitric oxide synthases (eNOS and nNOS), Cu/Zn-superoxide dismutase (SOD) and manganese-SOD (Mn-SOD) were evaluated. We also assessed in plasma: lipid profile, glycemia and malondialdehyde (MDA) levels. The nitrite/nitrate (NOx-) levels were measured in both plasma and cytosol fraction of the gastrocnemius muscle.Key findings: 8-week L-arginine supplementation associated with physical training was effective in promoting greater tolerance to exercise that was accompanied by up-regulation of the protein expressions of mtTFA, PGC-1 alpha, ATP synthase subunit c, COXIV, Cu/Zn-SOD and Mn-SOD. The upstream pathway was associated with improvement of NO bioavailability, but not in NO production since no changes in nNOS or eNOS protein expressions were observed.Significance: This combination would be an alternative approach for preventing cardiometabolic diseases given that in overt diseases a profound impairment in the physical performance of the patients is observed. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: Nitric oxide; Mitochondria; Physical training; Antioxidant enzymes; ATP synthase subunit c; Skeletal muscle